2011
DOI: 10.1029/2010ja016414
|View full text |Cite
|
Sign up to set email alerts
|

Millstone Hill ISR observations of upper atmospheric long-term changes: Height dependency

Abstract: [1] Ionospheric ion temperature is an excellent approximation to neutral temperature in the upper atmosphere, especially, for altitudes below 300 km. This analysis of long-term ionospheric ion temperature changes between 100 and 550 km at noon is based on a database of incoherent scatter radar observations spanning more than three solar cycles during 1968-2006 at Millstone Hill and provides direct evidence of long-term changes and their height dependency in the upper atmospheric temperature. A cooling trend at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
94
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(111 citation statements)
references
References 44 publications
14
94
3
Order By: Relevance
“…The subsequent atmospheric contraction would cause a lowering of ionospheric layers and a decrease in neutral density at fixed height (Rishbeth & Roble 1992), while the maximum electron density of ionospheric layers should not be affected much (Rishbeth 1990;Rishbeth & Roble 1992). Observational evidence has confirmed many of these predictions, at least in a qualitative sense: the global mean neutral density at fixed heights of 250-400 km has been decreasing (Keating et al 2000;Emmert et al 2004;Emmert & Picone 2011), the ion temperature, which is closely coupled to the neutral temperature, has been decreasing at several stations (Donaldson et al 2010;Zhang et al 2011;Zhang & Holt 2013), and at many stations decreasing trends in the heights of the maximum electron density of the ionospheric E and F 2 layers have been found (Bremer 1992(Bremer , 2008Ulich & Turunen 1997;Jarvis et al 1998;Bremer et al 2012). It has also been suggested that the changes in the ionosphere arising from increased greenhouse gases could be responsible, at least partly, for observed longterm changes in the daily amplitude of magnetic perturbations associated with the solar quiet (Sq) current system flowing in the low-to mid-latitude dayside ionosphere (Torta et al 2009;Elias et al 2010).…”
Section: Introductionsupporting
confidence: 55%
“…The subsequent atmospheric contraction would cause a lowering of ionospheric layers and a decrease in neutral density at fixed height (Rishbeth & Roble 1992), while the maximum electron density of ionospheric layers should not be affected much (Rishbeth 1990;Rishbeth & Roble 1992). Observational evidence has confirmed many of these predictions, at least in a qualitative sense: the global mean neutral density at fixed heights of 250-400 km has been decreasing (Keating et al 2000;Emmert et al 2004;Emmert & Picone 2011), the ion temperature, which is closely coupled to the neutral temperature, has been decreasing at several stations (Donaldson et al 2010;Zhang et al 2011;Zhang & Holt 2013), and at many stations decreasing trends in the heights of the maximum electron density of the ionospheric E and F 2 layers have been found (Bremer 1992(Bremer , 2008Ulich & Turunen 1997;Jarvis et al 1998;Bremer et al 2012). It has also been suggested that the changes in the ionosphere arising from increased greenhouse gases could be responsible, at least partly, for observed longterm changes in the daily amplitude of magnetic perturbations associated with the solar quiet (Sq) current system flowing in the low-to mid-latitude dayside ionosphere (Torta et al 2009;Elias et al 2010).…”
Section: Introductionsupporting
confidence: 55%
“…Merzylakov et al (2009) found a breakpoint in the semidiurnal tide above Obninsk and Collm around 1979, when the O 3 trend changed. Zhang et al (2011) have noted that the thermospheric cooling trend that they see in a 1968-2006 timeline from Millstone Hill did not emerge until the 1980s. The Fig.…”
Section: Discussion Of Trendlinesmentioning
confidence: 99%
“…Taking into consideration the complicity in the thermospheric and ionospheric responses to various energy inputs, current modeling of the ionosphere may thus require revision to capture the contribution of an inactive Sun as well as the widely concerned impact of greenhouse gases and the long-term trend of evolution of the neutral and ionized upper atmosphere (e.g., Laštovička, 2012Laštovička, , 2013Zhang et al, 2011;Zhang and Holt, 2013). An ultra weak solar cycle or grand solar minimum will also provide a suitable moment for researchers to continue with the investigation of non-solar forcing made during the declining phase and minimum of SC23, which have greatly improved our understanding of energy coupling between the lower and upper atmospheres (see the review articles by Laštovička, 2009 andPancheva andMukhtarov, 2012).…”
Section: Vision For Solar Cycle 24 and Beyondmentioning
confidence: 99%